Penguatan Desa Model Smart Village Berbasis Teknologi Informasi dan Komunikasi - Mai Puspadyna Bilyastuti; Suyani; Agus Suryanto; Tutik Heriana; Imam Nawawi; Asyifa’u Yuanita (I-Com: Indonesian Community Journal, 2023)
ABSTRACT The smart village model is one of the E-Government developments at the village level and is understood as an effort to empower, strengthen institutions and improve the welfare of rural communities by utilizing information technology. This service was carried out in Tugu Village, Mlarak District, Ponorogo Regency. The implementation of services at the Tugu Village office uses adequate IT equipment and the internet network is accessible in every hamlet, however in terms of disseminating public information regarding village profiles, village potential and village activities, social media such as YouTube has not been utilized. The results of this service activity are (1) creating a YouTube account and village profile as a means of disseminating information quickly, easily and effectively, (2) Installing online surveillance cameras (CCTV) around the village office and village hall. (3) increasing knowledge, especially PKK Akademia in making interesting videos to upload on social media (YouTube), (4) Increasing knowledge of using online surveillance cameras (CCTV) on smartphones.